Uit Marokko : De Aarde en haar Volken, 1906 - Genthe, Siegfried, 1870-1904 (Salt Lake City, UT : Project Gutenberg, 2004)
"Uit Marokko" by Siegfried Genthe is a travelogue written during the early 20th century. The book explores the cultural contrasts and historical context of Morocco, particularly the complexities of its relationship with Europe, especially Spain. Genthe delves into Morocco's unique societal structures and its enduring Islamic identity, contrasting it with European influences that have touched its shores yet failed to penetrate its deeper societal fabric. The opening of the book immerses the reader in the stark geographical and cultural dichotomy of the Strait of Gibraltar, serving as a gateway between Europe and Africa. It establishes a narrative focused on Genthe's reflections about Morocco's historical resilience, particularly the enduring presence of the Berber population amidst repeated foreign invasions. As Genthe prepares for his journey into Morocco, he describes his encounters in the coastal city of Tangier, where he feels the palpable tension between Moroccan tradition and European influence. This sets the stage for his subsequent adventures deeper into the country, framed by a rich backdrop of historical significance and cultural nuance. (This is an automatically generated summary.)
Release date is 2004-11-18
Produced by Jeroen Hellingman and the PG Distributed Proofreaders Team
Keywords: Morocco -- Description and travel